Efficacy and safety of 308-nm Excimer lamp combined with Tacrolimus 0.1% ointment vs Tacrolimus 0.1% ointment as monotherapy in treating children with limited vitiligo: a randomized controlled trial - Diala Alshiyab; Saleh A. Ba-shammakh; Abdulqudos Al-Fakih; Osama Tashman; Danyah Sarakbi; Firas Al-qarqaz; Jihan Muhaidat; Ausama Atwan; Michael J. Cork (Taylor & Francis Group, 2024)
AbstractObjective This study aims to assess the efficacy and safety of combining the 308-nm Excimer lamp with Tacrolimus 0.1% ointment, compared to Tacrolimus 0.1% ointment monotherapy, for treating pediatric vitiligo involving less than 10% of the body surface area.Methods Fifty pediatric patients with vitiligo were randomly assigned to two groups. Group A received Tacrolimus 0.1% ointment twice daily and Excimer light at 308-nm twice weekly, while Group B received Tacrolimus 0.1% ointment alone, administered twice daily. Repigmentation percentages were evaluated after 30, 90, and 180 days using the rule of nine.Results Group A exhibited a significant improvement in repigmentation, increasing from 10% after one month to 65% after six months. In contrast, Group B observed an increase from 10% to 30% over the same timeframe. The efficacy of the treatment was significantly higher in Group A at both the 3-month and 6-month follow-up points (p-value < .001). Moreover, Group A achieved notably higher repigmentation rates in the face, trunk, and lower limbs.Conclusion The combination of Tacrolimus and the 308-nm excimer lamp yielded superior repigmentation results compared to Tacrolimus monotherapy in pediatric vitiligo patients. This combined approach may offer an effective new treatment protocol for pediatric vitiligo.